Do Entrepreneurs’ Developmental Job Challenges Enhance Venture Performance in Emerging Industries? A Mediated Moderation Model of Entrepreneurial Action Learning and Entrepreneurial Experience - Chen, Yanni; Pan, Jianying (Frontiers in Psychology, 2019)
Drawing on work experience theory and human capital theory, we developed a model of how developmental job challenges enhance venture performance. Specifically, we developed and tested a mediated moderation model of developmental job challenges linking entrepreneurial action learning, entrepreneurial experience and venture performance. Based on a sample of Chinese entrepreneurs in emerging industries, we demonstrated that the developmental quality of entrepreneurial tasks had a positive relationship with venture performance and that this relationship was mediated by entrepreneurial action learning. Furthermore, we found that entrepreneurs with prior entrepreneurial experience were more likely to engage in entrepreneurial action learning behaviors and achieved better venture performance.